Design of low power PLL synthesizer for 60 GHz applications - Mahalingam, Nagarajan (2016)
The 60 GHz unlicensed band has attracted both the industry and researchers worldwide in realizing applications with multi giga-bits-per-second (Gbps) data rates. The advancement in integrated circuit (IC) design technology has further enabled the circuit designers to fully integrate the circuits for 60 GHz application on silicon. Also, the increased usage of handheld and smart devices requires the power consumption to be as low as possible.